Penyuluhan Gaya Hidup Sehat dan Bahaya Narkoba di SMP Global Islamic School Al-Amin Gondanglegi dengan Metode Seminar dan Diskusi - Ummah, Roisatul; Iza, Nikmatul; Nisa, Khoirun (JPM PAMBUDI, 2024)
A healthy lifestyle is a long-term lifestyle choice with a good lifestyle with a commitment to doing several things to support the body's functions, thereby providing health effects for the body, while drug abuse is drug use that is done not for medicinal purposes, but because they want to enjoy it. influence, in excessive amounts. The purpose of conducting counseling activities on healthy lifestyles and the dangers of drugs at SMP Global Islamic School Al-Amin Gondanglegi using seminar and discussion methods is to increase students knowledge and insight so that they understand the importance of maintaining a healthy lifestyle and avoiding negative things such as drugs. Based on the target students as the target of counseling activities, it is concluded that counseling on healthy lifestyles and the dangers of drugs with lectures and discussions increases the active role of students in thinking critically about lifestyle and drug problems, besides that the counseling activities carried out add to the insight of students so that the results of counseling can be applied daily and students avoid the dangers of drugs that damage the future of the nation.